Comfort in the Role: The Core of Positive Veteran Teachers - Sarah Jefferson; Christina Gray; Geoffrey Lowe (MDPI AG, 2024)
Teacher career trajectory studies have identified a small group of positive veteran teachers who have maintained an ongoing enthusiasm for and commitment to teaching. Research into teacher career trajectory frameworks suggests that comfort in the role remains a core tenet in supporting their sense of professional identity. While studies have identified this, there is little research into the subtleties of this tenet and how this helps these positive veteran teachers remain committed to teaching. This article reports on the qualitative findings about comfort in the role in sustaining positive veteran teachers' commitment to teaching. Further, the article points to key support measures accessed by these teachers to maintain this commitment. The ability to identify what comprises comfort in the role may encourage curriculum organisations and executive school leadership to retain and capitalise on the skills of their positive veteran teachers. This research seeks to examine an important teacher education perspective that provides valuable examples for beginning and early career teachers of practical mechanisms for positive coping mechanisms and maintaining comfort in the role in the longer term in a dynamic and demanding profession.